The European Union: Sword or shield?: comparing counterterrorism law in the EU and the USA after 9/11 - Hamilton, Claire (Theoretical criminology, 2018)
Drawing on the developing literature on a ‘European penology' this article seeks to use counterterrorism as a lens through which to re-examine arguments concerning penal moderation in Europe. Counterterrorism measures adopted in the EU and the USA in the post-9/11 period are therefore scrutinized for the lessons they hold about the role of European values and institutions as a ‘shield' against punitiveness or indeed their ability to, swordlike, cut deep into citizens' freedoms. The resulting analysis raises questions about the need for a more refined approach to the question of ‘European' penal values as well as pointing up the continued existence of a culture of rights in the USA.